2005
DOI: 10.1002/nur.20102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of music therapy on women's physiologic measures, anxiety, and satisfaction during cesarean delivery

Abstract: The purpose of the study was to investigate the effects of music therapy on women's physiologic measures, level of anxiety, and satisfaction during cesarean delivery. Sixty-four women who were planning to have a cesarean delivery were randomly divided into an experimental and a control group. The experimental group received routine care and music therapy, whereas the control group received routine care only. Our results indicated that compared to the control group the experimental group had significantly lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 22 publications
7
79
0
9
Order By: Relevance
“…Women who are prone to become too anxious are the ones that should benefit the most. Other authors have reported similar results with music listening, concerning the psychological well-being, but not cortisol on pregnant women (Browning, 2000;Sidorenko, 2000;Chang and Chen, 2005;Chang et al, 2008).…”
Section: Interventionsupporting
confidence: 59%
“…Women who are prone to become too anxious are the ones that should benefit the most. Other authors have reported similar results with music listening, concerning the psychological well-being, but not cortisol on pregnant women (Browning, 2000;Sidorenko, 2000;Chang and Chen, 2005;Chang et al, 2008).…”
Section: Interventionsupporting
confidence: 59%
“…Whereas Phumdoung and Good [40] were able to demonstrate a positive effect on the expectant mother during the active phase of labour, Liu et al [23] showed that the music intervention resulted in a reduction of pain and anxiety only during the latent phase and not during the active phase. Chang and Chen [49] discovered that a music intervention during caesarean section resulted in positive changes in the women, whereas Reza et al [48] with a similar intervention during the caesarean section did not achieve any results which would allow the conclusion of a positive effect of the music at the time of surgery. Further studies are required here in order to reach clearer conclusions regarding the ideal moment of music delivery and optimal duration of music interventions in obstetrics.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas Reza et al [48] showed that, from the induction of anaesthesia to skin suture, music intervention had no positive effects, Chang and Chen [49] found a positive effect of music intervention during the operation on the womenʼs feelings of anxiety and satisfaction. In the study by Reza et al [48], ▶ …”
Section: Music During Caesarean Sectionsmentioning
confidence: 99%
See 2 more Smart Citations